Variation in Penile Hemodynamics by Anatomic Location of Cavernosal Artery Imaging in Penile Duplex Doppler Ultrasound. (1st September 2015) - Pagano, Matthew J.; Stahl, Peter J.
Abstract: Introduction: Standard operating procedures (SOP) for penile duplex Doppler ultrasound (PDDU) were published in 2013 to promote uniform vascular assessment for erectile dysfunction (ED). However, SOPs do not specify a standard anatomic location for cavernosal artery (CA) imaging. Aim: The aim of this study was to determine the effects of CA imaging location on measured penile hemodynamics assessed by PDDU. Methods: PDDU was performed in men with ED and/or Peyronie's disease. CA peak systolic velocity (PSV) and end diastolic velocity (EDV) were measured at three points: the origin of the CA within the penile crus, the proximal CA, and mid‐CA. Differences in PSV and EDV were assessed by Friedman test and categorical vascular outcomes by Fisher's exact test. Data were analyzed for the main cohort, the subgroup with maximal smooth muscle relaxation (SMR) as defined by negative EDV, and the subgroup with valid‐for‐intromission erections. Main Outcome Measures: Mean PSV and EDV at three specified CA locations and the vascular diagnoses resulting from these measurements. Results: One hundred four CAs were imaged in 52 men. Mean PSVs at the crus, proximal, and mid‐CA were 52.9 ± 20.2, 29.5 ± 15.1, and 21.6 ± 10.6 cm/s, respectively ( P < 0.0001); mean EDVs were 2.1 ± 8.9, 3.2 ± 5.4, and 3.3 ± 3.5 cm/s, respectively ( P = 0.1225). The distribution of arteriogenic ( P < 0.0001) and venogenic ( P < 0.0001) diagnoses both differed significantly by location. Significant differences in vasculogenic diagnoses were also observed in the subgroup of CAs with definite maximal SMR (n = 38, arteriogenic P < 0.0001, venogenic P = 0.007) and in those with valid‐for‐intromission erections (n = 68, arteriogenic P < 0.0001, venogenic P = 0.0002). Conclusion: There is large variability in measured PSV and EDV on PDDU depending on the site of Doppler imaging, which can often sway clinical diagnosis. Future guidelines should attempt to incorporate standard locations of CA imaging, and new normative values may be necessary for each location.